Cómo planificar, diseñar y organizar un centro de cirugía ambulatoria. - González, Alejandro; de la Fuente, Natalia; del Río, Esteban; Zamora, Maximiliano; Nazar, Claudio (Revista Chilena de Cirugia, 2016)
Ambulatory surgery centers have contributed to the progress of ambulatory surgery and they are characterized by its efficiency, productivity and to produce high satisfaction. To build an outpatient surgery center a multidisciplinary team should be responsible to develop a project that to assess the economic viability, to select the type of center, to determine the size and the design of center and to set de staffing; with this information the final economic evaluation that decide the feasibility to build the center must be performed. To organize the launch activities and the operation of this service requires determining schedules, working mode, traffic flows and staff functions through protocols that to define, to describe and to coordinate all clinic and administrative process involved from the surgery indication to the patient discharge. The operating room efficiency is determining factor in the ambulatory surgery center functioning. Several factors contribute to the operating room efficiency, the most critical of which is the time between surgical procedures o turnover time and this time is feasible to optimize. Ambulatory surgery is a mode of surgical work requiring its own clinical service properly planned, designed and organized to achieve its objectives and advantages.